Pengaruh Teknik Modelling dengan Pendekatan Kontekstual Terhadap Keterampilan Menulis Teks Eksposisi Pada Peserta Didik Fase E - Andryani, Yulita (Jurnal Artikula, 2025)
Modeling Technique with Contextual Approach to Writing Skills of Expository Text of Grade X High School Students. This study was conducted based on the problem of low expository teks writing skills in high school students, difficulty in creative thinking in high school students which is characterized by students having difficulty in working on questions that are different from those exemplified by their teachers. This study aims to determine the difference in the influence of writing skills of students who learn using modeling techniques with students using demonstration techniques. The method in this study uses a quantitative method. The population and sample in this study were 2 classes of grade X students of SMA Negeri 2 Malingping who were selected randomly or Random Sampling. The instrument used in this study was an expository text writing skills test. The test used was a descriptive type test. Based on the result of the data analysis of the result of this study, the following conclusions were obtained. There is a difference in the influence of expository text writing skills of students who learn using modeling techniques with students who learn using demonstration technique learning are better than students who learn using demonstration techniques. This can be seen from the results of the hypothesis test, namely by using the Mann-Whitney Test from the Gain score data results that the results obtained Asymp Sig value 0,005 < 0,05 means H0 is rejected and H1 is accapted. So it can be stated that there is a significant difference in the increase in the influence of Modeling Techniques with a Contextual Approach to the Writing Skills of High School Students Exposition Texts